2017
DOI: 10.1016/j.msea.2017.01.092
|View full text |Cite
|
Sign up to set email alerts
|

Image-based correlation between the meso-scale structure and deformation of closed-cell foam

Abstract: In the correlation between structural parameters and compressive behaviour of cellular materials, previous studies have mostly focused on averaged structural parameters and bulk material properties for different samples. This study focuses on the meso-scale correlation between structure and deformation in a 2D foam sample generated from a computed tomography slice of Alporas TM foam, for which quasi-static compression was simulated using 2D image-based finite element modelling. First, a comprehensive meso-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…local density variation) in foam samples is considered. Previous 3D characterisation of Alporas foam using X-ray tomography showed that the axial variation in the local relative density of Alporas foam is less than 3% (Saadatfar et al, 2012), and similar observation was reported by Sun et al (2017) who analysed the local relative density distribution using X-ray tomography slice of Alporas foam. Therefore, the stochastic variation in local relative density cannot be the cause of the observed significant differences in the measured compressive properties shown in Figs.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
See 2 more Smart Citations
“…local density variation) in foam samples is considered. Previous 3D characterisation of Alporas foam using X-ray tomography showed that the axial variation in the local relative density of Alporas foam is less than 3% (Saadatfar et al, 2012), and similar observation was reported by Sun et al (2017) who analysed the local relative density distribution using X-ray tomography slice of Alporas foam. Therefore, the stochastic variation in local relative density cannot be the cause of the observed significant differences in the measured compressive properties shown in Figs.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…In contrast, the peak and plateau of compressive stress are similar between the samples prepared by different cutting methods. Considerable scatter in compressive stress-strain curves is observed, which can be attributed to both the scatter in relative density (Table 1) and the inherent heterogeneity of foam structures (Ramamurty and Paul, 2004;Sun et al, 2017).…”
Section: Cut-surface Profile and Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a conceptual equivalence between the macroscopic local strain and mesoscopic global strain for cellular materials has been applied in experimental strain mapping using digital image correlation [18,19], and in numerical strain calculations based on the cross-sectional displacement [20,21] and finite element nodal distance in a cell neighbourhood [22,23]. Similarly, the mesoscopic local strain and the microscopic global strain are equivalent, and they are both a measure of the deformation of the base material [21,[24][25][26]. This conceptual equivalence, again, acts as the link between the meso-scale and micro-scale.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is evident that, in the quasi-static and transitional dynamic regimes, the first crush band forms in the presumably weakest sites and then more crush bands form in other sites which are separate from or adjacent to the first band. The weakest sites can be identified by examining the mesoscopic structural heterogeneity or imperfection[21,207]. The localised deformation is randomly distributed in the sample.…”
mentioning
confidence: 99%